A novel endogenous damage signal, glycyl tRNA synthetase, activates multiple beneficial functions of mesenchymal stem cells. Issue 11 (November 2018) - Park, Se-Ra; Kim, Hyun-jin; Yang, Se-Ran; Park, Chan; Lee, Hwa-Yong; Hong, In-Sun
Abstract During tissue repair, the injury site releases various bioactive molecules as damage signals to actively recruit stem cells to the damaged region. Despite convincing evidence that mesenchymal stem cells (MSCs) can sense damage signals and promote repair processes, the identity of these signals and how these signals regulate stem cell-mediated tissue repair remain unknown. Glycyl tRNA synthetase (GRS) is a ubiquitously expressed enzyme that catalyzes the first step of protein synthesis in all organisms. In addition to this canonical function, we identified for the first time that GRS is released by damaged tissues or cells in response to various injury signals and may function as a damage signal that activates the proliferative, differentiation, and migratory potential of MSCs, possibly through its identified receptor, cadherin-6 (CDH-6). Binding between GRS and CDH-6 activates survival signals, such as those of the PI3K/Akt and/or FAK/ERK1/2 pathways. More importantly, we also found that MSCs stimulated with GRS show significantly improved homing and differentiation potential and subsequent in vivo therapeutic effects, in a liver fibrosis animal model. Collectively, our findings provide compelling evidence for a novel function of GRS in enhancing the multiple beneficial functions of stem cells via a non-canonical mechanism as a damage signal.